An assessment study on various clean hydrogen production methods - Aydin, Muhammed Iberia; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
In this study, an assessment study using the life cycle impact analysis of renewable and nuclear-based hydrogen production methods is conducted for possible implementation of hydrogen energy projects. The processes starting from the energy production, energy required for the hydrogen production, hydrogen transportation, and utilizing hydrogen at the refueling station are evaluated. The three methods, namely alkaline electrolysis, proton exchange membrane electrolysis, and the Cu-Cl cycle are selected as clean hydrogen production methods. Also, the potential environmental effects of using hydrogen to utilize fuel cell electric buses are investigated by comparing them with diesel buses. Accordingly, the Cu-Cl cycle itself provides the most environmentally friendly result with 0.86 kg CO2 eq./kg H-2 when both energy and heat are considered as primary commodities from renewable energy sources. However, the electrolysis methods also provide better results than conventional hydrogen production. By comparison, conventional hydrogen production resulted in 7.95 kg CO2 eq./kg H-2. The emissions of FCEBs utilizing the hydrogen from clean energy sources vary between 0.016 and 0.025 kg CO2 eq./p.km. However, even though upstream emissions are low in diesel buses, they have a GWP value of approximately 0.09 kg CO2 eq./p.km during operation. (C)& nbsp;2021 Published by Elsevier Ltd.
Keywords: Energy; Hydrogen; Fuel cells; Renewables; Nuclear energy; Sustainable development; Life cycle assessment; Environmental impact; LIFE-CYCLE ASSESSMENT; CU-CL CYCLE; FUEL-CELL; DIESEL; GAS; ELECTROLYSIS; EMISSIONS; Thermodynamics; Energy & Fuels